Cumulative author index 1993–2003 (Condensed Matter Physics, 2003)
During 1993–1997 the journal had only issue numeration (issues 1–12). Starting from 1998 the volume/number numeration is used. However, for backward compatibility the sequential issue number of the journal is still indicated in parenthesis.